Risk factors associated with hypertensive disorders in pregnancy in Nekemte referral hospital, from July 2015 to June 2017, Ethiopia: case-control study - Leta Hinkosa; Almaz Tamene; Negeso Gebeyehu (BMC, 2020)
Abstract Background Hypertension is the most common medical problem encountered in pregnancy and is a leading cause of perinatal and maternal morbidity and mortality. However, its magnitude and risk factors yet not adequately assessed at the study area. Methods Facility-based retrospective unmatched case-control study was conducted to identify risk factors associated with Hypertensive disorders of pregnancy in Nekemte Referral Hospital just two years back from study period July 1, 2015, to June 30, 2017. Bivariate logistic regression was considered for inclusion in to the multivariate logistic regression. Finally, multi varaite analysis were done to identify risk factors of hypertensive disorders of pregnancy. Results Among 6826 total delivery records from July 2015 -June 2017, 199 women developed hypertension during pregnancy. Among 199 women 153(76.9%) were pre-eclampsia/eclampsia,28(14.1%) were gestational hypertension, 14(0.7%) were superimposed hypertension and 4 (2.9%) were chronic hypertension. Age ≥ 35 (AOR: 2.51, 95% CI: 1.08, 5.83), rural residential area (AOR: 1.79, 95% CI: 1.150, 2.799), prim gravida (AOR: 3.39, 95% CI: 2.16, 5.33), null parity (AOR: 4.35, 95% CI: 2.36, 8.03), positive history of abortion (AOR: 4.39, 95% CI: 1.64, 11.76), twin pregnancy (AOR: 3.78, 95% CI: 1.52, 9.39), lack of ANC follow up (AOR: 3.05, 95% CI: 1.56, 5.96) as well as positive pre-existing hypertension (AOR: 3.81, 95% CI: 1.69, 8.58), positive family history of hypertension (AOR: 5.04, 95% CI: 2.66, 9.56) and positive history of diabetes mellitus (AOR: 5.03, 95% CI: 1.59, 15.89) were risk factors for hypertensive disorders during pregnancy. Conclusion This study found that Women with hypertension during pregnancy have a greater risk of developing adverse pregnancy outcome as compared to normotensive pregnant women. so, identification of these risk factors would be useful for early diagnosis of hypertension disorders during pregnancy to give appropriate clinical monitoring and treatments and timely managing maternal and perinatal complications.